군 의무장교들의 군지역 보건간호사업에 대한 필요성 인식도 조사연구 - 정정화 (연세대학교 보건대학원, 1987)
[한글] 사회가 발전함에 따라 보건사업도 변모하여 입원환자 중심의 병원치료 사업에서 가족 및 지역사회를 대상으로 질병의 예방, 건강보호와 유지, 증진을 도모하는 포괄적인 건강사업이 요청되고 있다. 이에 군간호 병과에서도 이러한 변화에 부응하기 위하여 1986년 말부터 보건간호사업 군 도입을 위한 연구를 계속해 왔다. 그러나 보건사업은 팀접근이 중요한 요소이므로 군 보건간호사업 실시 시에 군의, 의정, 간호병과는 중요한 팀요원이 된다. 그러므로 이들이 인식하고 있는 군 보건간호사업의 내용을 파악하여 군 보건간호사업 계획시안을 마련하는데 기초 자료를 제공하고자하여 본 연구를 시도하였다. 연구에 이용된 도구는 본 연구자에 의해 개발된 질문지로 타당도 검정을 거친 설문지였고 연구기간은 1987년 10월 12일에서 24일까지 12일간 이였다. 연구방법은 전국에 있는 국군병원중 무작위 추출된 3개 병원에 근무하는 000명의 의무장교를 대상으로한 설문조사였으며 군의병과 89명, 의정병과 43명, 간호병과 157명에 대한 자료를 분석, 비교한 결과는 아래와 같다. 1. 조사대상자의 일반적 특성은(계급, 군복무기간, 결혼상태, 출신지, 군종사예정기간, 전방근무경험)세 병과 간에 유의한 차이가 있었다. 2. 군 보건의료사업에 대한 만족도는 전반적으로 낮은 편이였으며 그중 의정장교보다는 군의나 간호병과에서 더 낮게 평가하였다. 현재 보건간호장교가 있다는 사실은 군의관 군에서 가장 낮게 나타났으나, 보간장교 업무 협조 정도는 세개 병과 공히 높았다. 3. 군 보건간호장교 업무에 대한 앞으로의 협조 정도는 보건진료원 제도에 대한필요성, 예방중심의 건강 사업, 찬성여부, 군지역사회 보건간호사업 필요성과 높은 순 상관관계를 보였다. 4. 가장 필요한 보건간호사업 항목은 보건교육에 필요한 교육자료개발(4.371±.698)이었고, 입원환자 퇴원시의 보건교육 계획항목(3.091±.999)이 가장 필요성이 낮았다. 5. 병과별로 군 보건간호사업에 필요하다고한 사업 영역을 보면 군의관 군에서는 환경위생 관리 영역 (3.89±1.37), 의정장교 군에서는 전염병 관리 영역(4.26±.73),간호장교 군에서는 보건교육 영역 (4.35±.67)을 각각 필요성이 높은 사업으로 인지하였다. 6. 사업 영역별 제변수간에는 모두 정상관관계를 나타냈으며, 환경위생 관리와 전염병 관리 영역 (γ=.5789)간에 가장 높은 상관관계를 나타냈다. 7. 필요한 군 보건간호사업에 대한 보건간호직무인지는 부대방문 보건교육 (92.O%)이 가장 높았고, 반면 부대숙소 환경 관리 (64.3%)가 가장 낮았다. 8. 병과별 필요한 군 보건간호사업 영역에 대한 보건간호장교 직무인지를 보면 군의관 군에서는 59.5%로 건강상담 영역을, 의정 장교 군에서는 76.9% 에서 모자보건 영역, 간호장교 군에서는 87.3%로 만성질환 관리 영역을 각각보건간호장교 직무로 높게 인지했다. 9. 필요한 사업 우선순위와 보건간호장교 직무 우선순위는 일치하여 필요한 사업 우선순위가 높을수록 보건간호장교 직무 우선순위도 높았다. 이상의 결과를 종합해 보면 보건교육에 관한 사업항목이 가장 필요한 군 보건간호사업으로 높게 인지되었다. 그러므로 이 연구 결과를 토대로 하여 군 지역 보건간호사업 계획 시안을 제시하고자 하며, 보다 합리적인 계획안이 되기 위해서는 보건의료 사업 대상자 들에 대한 건강요구 사정이 병행되어야 한다. [영문] According to social development, the contents of health services, from the hospital-oriented health services only for in-patients to the family and community-centered service for the prevention of disease and enhancement of health state, have been changed. At the same time, comprehensive health services have been needed, spontaneously. In order to fellow these changes, the Korean army nurse corps have studied for practicing the community health nursing services in the army since the late of 1986. However, team approach is basic element in practicing successful health services. The medical, medical administrative and nurse officer's sections are important team personnel among 5 military medical sections, Therefore, this study were designed for finding what kinds of service of community health nursing they perceived to be needed and for providing basic material in establishing plan for the community health nursing services. The questionaires that made by this researcher and were done validity test was used as tool for this study. The subjects was 289 medical section's officers. Data for this study were corrected over a period of 12 days from 12th of October, to 24th of October, 1987., and were analyzed and cam pared between 89 medical officer's group, 43 medical administrative officer's group and 157 nurse officer's group. The major finding were summarized as follows: 1. There were significant differences in general character (Rank, experienced service years, marital status, etc.) between three groups. 2. The Satisfaction of military health services were low generally, medical surgeon and nurse officer's groups was lower than medical administrative officer's group. The existence of community health nurse in the Korean army were perceived the lowest in the medical surgeon group. And the cooperation of community health nurse. s jobs was high in all groups. 3. There were high correlation between the necessity of the community health nurse practioner, the agreement of preventive health services and the necessity of community health nursing services in the army and the cooperation of community health nurse's job in the future. 4. As the needed item for military community health nursing services, the item of the development of the educational materials for health education (4.371±.698) were get the highest score, on the other hand the item of the planning of health teaching for in-patients (3.091±.999) were get the lowest score. 5. As the needed category for military community health nursing service, the category related to the control of environmental hygiene (3.89±1.37)in medical surgeon group, the control of communicable disease (4.26±.73)in medical administrative officer's group and the category of health education(4.35±.67) in nurse officer's group were get the highest score, respectively. 6. There were correlation between all 8 categories of the military community health nursing services, respectively. The correlation between the control of environmental hygiene and the control of communicable disease were the highest (r=.5789). 7. The item of the visiting health education (92.0%) were get the highest rat, on the other hand the item of the control of environmental hygiene for military housing (64.3%) were get the lowest rate as the community health nurse's jobs among 29 items of military community health nursing. 8. The category related to health counseling 59.5% in medical surgeon's group, the category of maternity and child health service 76.9% in medical administrative officer's group and the care of chronic disease 87.3% in nurse officer's group were perceived highly as the community health nurse's jobs in 8 categories, respectively, 9. There were rank correlation between the priority of the item of military health nursing service that needed and the priority of community health nurse's jobs in 29 items In summarizing the above result, the item related to health education were perceived highly as the needed service programs for military community health nursing. The plan for the practicing community health nursing service in the army would be established as based on the result. Further study is needed to be more systematic plan, that is not only health care providers but also health care consummers for assessment of their health need are needed to be study subject.
보건학과/석사